From Egypt to Zagreb. The history of Roman Catholic orders in the Balkans - Lotmentsev, Andrey M. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The article examines the problem of the development of mendicant orders in Central Europe, mainly in Croatia, Slavonia and Bosnia. The author suggests that the activities of the mendicant orders in the 13th century became one of the most impressive achievements of the Roman Papacy in the Middle Ages. In particular, the Franciscans were able not only to adapt to living conditions in different regions of Italy, but also rapidly established their presence throughout Europe and then beyond. In the future, mendicant monks will play an important role in defending the Balkans from the Ottoman Turks while repelling the attacks of the Ottoman Sultan Mehmed Fatih. But already in the middle of the 13th century, the Franciscans and Dominicans became an important integrating factor and greatly contributed to the urbanization of many countries. Despite the fact that the history of the mendicant orders has been actively studied in Catholic historiography, many aspects of their settlement and influence on the regions have remained unexplored due to the very specifics of their work.